Human Response to Primate Deviance - Zeller, Anne C. (Anthropologica, 2022)
If it is difficult enough for students of human behaviour to agree on a definition of deviance, it is more so when the subject of discussion is non-human primates. Deviant behaviour among primates is usually equated with "abnormal" behaviour, which impedes Darwinian fitness. Deviance may consist either in passivity and with drawal or in hyperactive, aggressive behaviour. The classification of particular behaviours as deviant depends on the environment in which the primates live, e.g., caged or free-ranging, and on the perspective and interests of the researchers, e.g., zoo-keepers, veterinarians and researchers who work with either caged or free-ranging animals. Nonetheless, there are certain behaviours which virtually all scholars would classify as deviant or abnormal.